The Relationship between Nonalcoholic Fatty Liver Disease and Colorectal Cancer: The Future Challenges and Outcomes of the Metabolic Syndrome - Said O. Muhidin; Ahmed A. Magan; Khalid A. Osman; Shareef Syed; Mohamed H. Ahmed (Journal of Obesity)
Nonalcoholic fatty liver disease (NAFLD) is closely related to insulin resistance, metabolic syndrome, obesity, type 2 diabetes, and dyslipidaemia. Obesity and metabolic syndrome are associated with an increased cancer risk, and recent evidence demonstrated an association between NAFLD and colorectal cancer (CRC). The mechanism of how NAFLD can be associated with increased risk of CRC is not fully understood; however, NAFLD represents a condition of profound insulin resistance and a proinflammatory state. Insulin and insulin-like growth factors may promote the development of CRC through their proliferative and antiapoptotic effects. Patients with NAFLD have reduced expression of adiponectin, an adipokine with anti-inflammatory effects. Importantly, hypoadiponectinemia is associated with an increased risk of CRC. Decreased levels of adiponectin lead to increased insulin levels due to marked insulin resistance and in turn increased insulin growth factor-1 (IGF-1). Insulin binds to IGF-1 receptors and plays an important role in cell proliferation, apoptosis, and increased production of vascular endothelial growth factor, an angiogenic factor that supports cancer growth. Further studies are needed to establish (i) the pathophysiology of NAFLD with colorectal cancer, (ii) the benefit of early screening of CRC in NAFLD patients, and (iii) the impact of treatment of NAFLD in the modulation of the risk of colorectal cancer.